1997
DOI: 10.1002/(sici)1097-0215(19970117)70:2<159::aid-ijc4>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Attributable risks for breast cancer in Italy: Education, family history and reproductive and hormonal factors

Abstract: The percent population attributable risk (AR) for breast cancer was estimated in relation to education, family history of the disease and some reproductive and hormonal factors, using data from a case-control study conducted between June 1991 and February 1994 in 6 Italian centres on 2,569 histologically confirmed incident breast cancer cases and 2,588 controls, admitted to hospital for a wide range of acute, nonneoplastic, non-hormone-related diseases. On the basis of multivariate odds ratios, a high level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 20 publications
8
35
3
Order By: Relevance
“…The well recognized risk factors for breast cancer (including age at menarche, age at menopause, parity, family history, alcohol drinking, body mass index, etc.) were consistently observed in the present data (47,48). Among the strengths of this study are the uniquely large dataset, the high intake of fruit and vegetables in the population, the satisfactory reproducibility and validity of the food frequency questionnaire (34,35), and the ability to control for total energy intake and major potential confounding factors.…”
Section: Discussionsupporting
confidence: 91%
“…The well recognized risk factors for breast cancer (including age at menarche, age at menopause, parity, family history, alcohol drinking, body mass index, etc.) were consistently observed in the present data (47,48). Among the strengths of this study are the uniquely large dataset, the high intake of fruit and vegetables in the population, the satisfactory reproducibility and validity of the food frequency questionnaire (34,35), and the ability to control for total energy intake and major potential confounding factors.…”
Section: Discussionsupporting
confidence: 91%
“…d Analyzed concentrations indicate the actual congener concentrations in the 1,000× dosing solution, measured in a blind test by Wellington Laboratories (Guelph, Ontario, Canada). e Amounts given to the neonates when gavaged with 5.18 mL/kg of the 1,000× mixture at day 1 (a cumulative dose equal to 1,000 times human baby intake at day 0, 1, 2, 3, 4), day 5 (a cumulative dose for day 5,6,7,8,9), day 10 (a cumulative dose for day 10,11,12,13,14), day 15 (a cumulative dose for day 15,16,17,18,19), and day 20 of age (a cumulative dose for day 20,21,22,23,24). f PCB congeners are separated according to the position of the chlorine substitution.…”
Section: Methodsmentioning
confidence: 99%
“…The acknowledged risk factors for breast cancer are genetic predispositions (3)(4)(5)(6) and reproductive factors (7,8). These risk factors account for only 30-50% of the cases (5,(9)(10)(11)(12); thus, environmental factors (exposure to manmade and natural chemicals, dietary habits, lifestyle) are hypothesized to account for the remaining cases.…”
mentioning
confidence: 99%
“…Age at first full-term pregnancy has been considered important to the risk of developing breast cancer by previous studies (Tavani et al, 1997;Kuru et al, 2002). In this study, the odds of developing breast cancer were found to be 0.39 times among women less than 18 years old at first pregnancy.…”
Section: Discussion:-mentioning
confidence: 48%
“…Hence, women with two or more deliveries were less likely to develop breast cancer compared to women who never has any delivery, although, the relationship was not statistically significant (P>0.005). Similarly, Tavani et al (1997) and Ebrahimi et al (2002) reported that breast cancer risk decreases with high parity. However, some studies of meta-analysis in Nordic countries and study conducted in Nigeria (Ewertz et al, 1990; Adebamowo and Adekunle, 1999), reported that no association was reported between risk of developing breast cancer and number of past deliveries among women studied.…”
Section: Discussion:-mentioning
confidence: 92%